Implementation of the Pancasila Student Profile Strengthening Project for Preserving Local Traditions at MTsN 17 Jombang - ‘Azah, Nur; Sholeh, Muh Ibnu; Aziz, Abdullah Aminuddin; Al-Fatih, Muhammad; Pratiwi, Emy Yunita Rahma; Masruroh, Laily (Yayasan Pendidikan Bima Berilmu, 2024)
This study aims to explore the implementation of the Pancasila Student Profile Strengthening Project (P5) in preserving local traditions at MTsN 17 Jombang, East Java. As part of the Merdeka Curriculum, P5 seeks to integrate Pancasila values, including respect for local culture, into the educational process. This research employs a qualitative approach with a case study design, involving in-depth interviews, participatory observation, and document analysis as data collection techniques. The subjects of the study include the school principal, teachers, students, and community leaders involved in the P5 implementation. The findings indicate that the implementation of P5 at MTsN 17 Jombang successfully integrates local traditions into the curriculum through various activities such as traditional dance training, traditional music, handicrafts, and ceremonial events. This project not only enhances students' awareness of local culture but also involves the community in the preservation of traditions. Challenges encountered include limited resources and time for extracurricular activities, as well as the need for teacher training in managing cultural preservation activities. The study concludes that P5 can be an effective model for preserving local traditions through formal education. With the right approach, P5 at MTsN 17 Jombang can serve as a best practice example for integrating local culture into school curricula. The findings are expected to contribute to the development of culturally-based curricula in other schools across Indonesia.